2013
DOI: 10.1271/bbb.130020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7-Oxo-5-deoxystrigol, a 7-Oxygenated Strigolactone Analog

Abstract: A straightforward synthesis of 7-oxo-5-deoxystrigol, a 7-oxygenated strigolactone analog, was achieved by starting from 2,2-dimethylcyclohexane-1,3-dione.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Racemic [6′-D]-5DS isomers (rac-d 1 -1 and rac-d 1 -2) and sorgomol isomers, 8-epi-sorgomol (7), 2′,8-bisepi-sorgomol (8), 2′-episorgomol (9), and 7-hydroxy-5DS (10), were prepared using the method reported previously. 11,22) Racemic [2-13 C,6′-D]-5DS (1a/1b) and its diastereomer, [2-13 C,6′-D]-4DO (2a/2b), were prepared according to the method reported previously. 23 13 C,6′-D]-ent-4DO (2b) were eluted at 16.9 and 19.9 min, respectively.…”
Section: Chemicalsmentioning
confidence: 99%
“…Racemic [6′-D]-5DS isomers (rac-d 1 -1 and rac-d 1 -2) and sorgomol isomers, 8-epi-sorgomol (7), 2′,8-bisepi-sorgomol (8), 2′-episorgomol (9), and 7-hydroxy-5DS (10), were prepared using the method reported previously. 11,22) Racemic [2-13 C,6′-D]-5DS (1a/1b) and its diastereomer, [2-13 C,6′-D]-4DO (2a/2b), were prepared according to the method reported previously. 23 13 C,6′-D]-ent-4DO (2b) were eluted at 16.9 and 19.9 min, respectively.…”
Section: Chemicalsmentioning
confidence: 99%
“…The strategy outlined above is generally applicable. This is demonstrated by the total synthesis of 7‐oxo‐5‐deoxystrigol . Once the starting material with an oxo group adjacent to the gem dimethyl has been obtained from 2,2‐dimethylcyclohexane‐1,3‐dione, the usual sequence of preparing the ABC scaffold and attaching the D‐ring was followed (Scheme ).…”
Section: Total Synthesis Of Natural Slsmentioning
confidence: 99%
“…In the same way, some plants species synthetize orobanchol by bioconversion of 4-deoxyorobanchol, although other species would synthetize it from another compound. Tanaka et al (2013) reported a synthetic strategy to obtain the analogue 7-oxo-5-deoxystrigol in 11 steps from 2,2-dimethylcyclohexane-1,3-dione (Scheme 27). This route starts with protection of one of the ketone groups, which is then transformed into a dienone by way of Grignard and oxidation reactions.…”
Section: Strigol Orobanchol and Sorgomol Familiesmentioning
confidence: 99%